Identification of the molecular targets and mechanisms of compound mylabris capsules for hepatocellular carcinoma treatment through network pharmacology and bioinformatics analysis. (10th August 2021) - Wei, Junwei; Ma, Luyuan; Liu, Wenpeng; Wang, Yadong; Shen, Chuan; Zhao, Xin; Zhao, Caiyan
Abstract: Ethnopharmacological relevance: Traditional Chinese herbal formulas have been proven to exert an inhibitory effect on tumor. Compound mylabris capsules (CMC) has been used for treating cancer, especially hepatocellular carcinoma (HCC), for years in China. However, its therapeutic mechanisms on HCC remain unclear. Aim of the study: This research aimed to elucidate the molecular targets and mechanisms of CMC for treating HCC. Materials and methods: First, the bioactive ingredients and potential targets of CMC, as well as HCC-related targets were retrieved from publicly available databases. Next, the overlapped genes between potential targets of CMC and HCC-related targets were determined using bioinformatics analysis. Then, networks of ingredient-target and gene-pathway were constructed. Finally, cell experiments were carried out to examine the effects of CMC-medicated serum on HCC and validate the core molecular targets. Results: In total, 151 bioactive ingredients and 255 potential targets of CMC were selected, 982 differentially expressed genes of HCC were identified. Among them, 34 overlapped genes were finally selected. In addition, 20 pathways and 429 GO terms were significantly enriched. Protein-protein interaction and gene-pathway networks indicated that Cyclin B1(CCNB1) and Cyclin Dependent Kinase 1(CDK1) were the core gene targets for the treatment of CMC on HCC. Moreover, in vitro studies showed that CMC-medicated serum significantly inhibited the viability of HepG2 cells. Furthermore, CMC downregulated CCNB1 and CDK1 expressions and induced G2 /M phase cell cycle arrest. Conclusions: CMC plays a therapeutic role in HCC via multi-component, -target and -pathway mechanisms, in which CCNB1 and CDK1 may be the core molecular targets. This study indicates that the integration of network pharmacology and bioinformatics analysis, followed by experimental validation, can serves as an effective tool for studying the therapeutic mechanisms of traditional Chinese medicine. Graphical abstract: Image 1